Clinical Management and Lifestyle Intervention for Hypertension in an Elderly Patient at a Primary Health Care Facility in Indonesia - Festy Ladyani; Susi; Yustira Mayasari; Welvin Kurniawan Susanto; Widi Anggaraini; Widya Karina Sari; Wijihan Rusi Nur Aulia; Windy Septrihani; Mikael Syväjärvi (Biomedical Research and Theory Letters, 2026)
Hypertension remains one of the most prevalent chronic non-communicable diseases worldwide and constitutes a major risk factor for cardiovascular morbidity and mortality, particularly among elderly populations. Despite the availability of effective antihypertensive therapies, blood pressure control remains suboptimal in many patients due to delayed diagnosis, inadequate treatment adherence, and unhealthy lifestyle practices. Primary health care facilities play a critical role in the early detection, management, and long-term monitoring of hypertension, especially in low- and middle-income settings. This study describes the clinical management and outcomes of an elderly patient with poorly controlled hypertension treated at a community-based primary health care center in Bandar Lampung, Indonesia. A 70-year-old woman presented with persistent headaches, dizziness, and fatigue lasting for approximately two weeks. Initial clinical assessment revealed elevated blood pressure of 170/90 mmHg. The patient had a five-year history of hypertension but reported inconsistent use of antihypertensive medication and suboptimal lifestyle behaviors, including frequent caffeine consumption and limited physical activity. Management involved pharmacological therapy using amlodipine at a daily dose of 5 mg, combined with comprehensive non-pharmacological interventions. The patient received individualized counseling focused on lifestyle modification, including dietary salt restriction, reduction of caffeine intake, encouragement of regular physical activity, and routine blood pressure monitoring. Emphasis was also placed on improving medication adherence through patient education and follow-up support. At a two-week follow-up evaluation, the patient demonstrated a clinically meaningful reduction in blood pressure to 150/80 mmHg, accompanied by a marked improvement in reported symptoms. Additionally, the patient showed enhanced understanding of hypertension management and greater adherence to dietary and lifestyle recommendations. These findings underscore the importance of integrated hypertension management strategies in primary care settings, particularly for elderly patients. The combination of appropriate pharmacological treatment, lifestyle modification, and patient education can significantly improve blood pressure control and reduce the risk of long-term complications. Strengthening primary care–based hypertension programs may contribute to better cardiovascular health outcomes at the community level.